Mapping a sequence diagram to the related code: cognitive levels expressed by developers - McMeekin, David; Von Konsky, Brian; Chang, Elizabeth; Cooper, David (IEEE, 2009)
This paper reports on a study in which developers? cognitive levels were categorised and measured while theymapped a sequence diagram to the related code based on a Usage Based Reading scenario. Results indicate that applying the usage-based reading technique to map a sequence diagram to the underlying code, facilitates a developer to operate at the Knowledge and Comprehension levels of Bloom?s cognitive taxonomy, but does not facilitate sustaining it at the Analysis level. The results of this study highlight the need for improved tools and methodologies that aid developers understanding of the system, particularly for those commencing a new project.